Salvaging the Lost Pink Triangle: A Case Series of Papilla Reconstruction - Santhosh Shenoy B; Anahita Punj; Amitha Ramesh; Avaneendra Talwar (Case Reports in Dentistry, 2020)
Introduction. The interdental papilla may be lost or reduced in height, forming black triangles due to various reasons, which gives an unaesthetic appearance when the patient smiles. Various noninvasive and invasive techniques have been used to augment/reconstruct the interdental papilla, to reclaim the pink triangle. The most satisfactory and natural appearance can be obtained by augmenting or reconstructing the lost papilla as the pink esthetics is as important as the white esthetics. Cases. Two female patients and 1 male patient reported to the dental department with the complaint of a small black gap in the gum area between their upper front teeth since 6 months and 1 year, respectively. On examination, the interdental papillae in all three cases were classified as class 1 (Nordland and Tarnow’s). The interdental papilla was augmented surgically by using three different approaches in each case. Result and Conclusion. Postoperatively and after 1-month follow-up, there was a complete fill of the interdental area by the interdental papilla normal (Nordland and Tarnow’s). As a result, the black triangle was successfully converted into a natural pink triangle in all three cases.